2013
DOI: 10.4103/0300-1652.126300
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and perinatal outcome of uterine rupture in a low-resource setting

Abstract: Background:Uterine rupture has continued to be a catastrophic feature of obstetric practice especially in the low-resource settings. This study determined the incidence, predisposing factors, treatment options and feto-maternal outcome of ruptured uterus.Materials and Methods:A 10-year retrolective study of all cases of uterine ruptures that were managed in Nnamdi Azikiwe University Teaching Hospital, Nnewi, Nigeria between 1st January, 2001 and 31st December, 2010 was undertaken. The proforma was initially us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 22 publications
4
30
1
1
Order By: Relevance
“…This is equivalent to case fatality rate of 1.5% similar to a study done in UK which reported a case fatality rate of 1.3% [33]. This is contrary to other studies done in Africa where maternal case fatality rates were reported to be high, 6% -16% [1,3,12,34].…”
Section: Maternal Outcomescontrasting
confidence: 41%
See 1 more Smart Citation
“…This is equivalent to case fatality rate of 1.5% similar to a study done in UK which reported a case fatality rate of 1.3% [33]. This is contrary to other studies done in Africa where maternal case fatality rates were reported to be high, 6% -16% [1,3,12,34].…”
Section: Maternal Outcomescontrasting
confidence: 41%
“…Uterine rupture is one of the major obstetric catastrophic events which may be associated with severe hemorrhage, hysterectomy, genitourinary injury and maternal death [1][2][3][4][5]. According to World Health Organization (WHO), the incidence of uterine rupture is high and a serious problem in developing countries ranging from 0.1% to 1% [4].…”
mentioning
confidence: 99%
“…Of those cases, 44.2% received oxytocin and had a prior uterine scar, 18.6% received oxytocin without having a prior scar, 13.9% received no oxytocin but had a prior scar, 9.3% had increased fundal pressure, 4.7% had an obstructed labour and 4.6% were identified as classical caesarean section patients. Of the ruptures, 88.4% were complete and 11.6% were incomplete …”
Section: Discussionmentioning
confidence: 99%
“…One study found 6.2 cases of uterine rupture per 1000 vaginal deliveries in women who had previously undergone a caesarean section . Another study of 5635 women found that uterine scar dehiscence did not increase the risk of uterine rupture …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation